An Analysis of Educational Programming for and Learning Outcomes - Abigail Marie Felber (Networks: An Online Journal for Teacher Research, 2009)
In order to better understand the educational outcomes of English language learners enrolled in two distinct programs at this school, the researcher, a 4th/5th grade bilingual teacher, studied leading research in the field of bilingual education, administered and analyzed assessments and interviewed participants’ families as well as colleagues. The premise of the study was to compare literacy levels of two sample groups—six students who received instruction solely in English and six students who received instruction both in English and Spanish. All students were Latino, and Spanish was the predominate language spoken in their homes. Study findings revealed that, regarding English literacy, students receiving instruction only in English showed slightly higher text reading levels in English, but all students performed similarly on the English writing assessment. In Spanish literacy, the assessment data revealed that students receiving instruction in both English and Spanish maintained and/or developed higher literacy skills in their first language than students who received instruction only in English. (Note: Assessments focused on writing and reading as opposed to all four domains of literacy—reading, writing, speaking and listening.)